how to multiply rational expression of (x^2 + xy / 15y^3) (35y^2 / 6x+6y) (12x / 10y^2

Guide :

how to multiply rational expression of (x^2 + xy / 15y^3) (35y^2 / 6x+6y) (12x / 10y^2

how to multiply rational expression

Research, Knowledge and Information :


how to multiply rational expression of (x^2 + xy / 15y^3 ...


how to multiply rational expression All Activity; Q&A; Questions; Unanswered ... (x^2 + xy / 15y^3) (35y^2 / 6x+6y) (12x / 10y^2) 0 votes. how to multiply rational ...
Read More At : www.mathskey.com...

multiply 2xy(x^2-xy+4) by applying the distributive property ...


multiply the following by applying the distributive property 2xy(x^2 ... to write an equivalent expression. A.) (3•y)•z B.) x + ... (x^2 + xy / 15y^3) (35y^2 / 6x ...
Read More At : www.mathskey.com...

y^2-16y+64=16 - page 2 - Jiskha Homework Help


What is the excluded value for the rational expression x^2 ... a= 3/2x-6=y 2. x+y=7 a= y=-x+7 3. -13+6y=x a= y=x/6+13/6 4. -2y ... the polynomial 6x^3 - 18x^2 + 12x ...
Read More At : www.jiskha.com...

Factor Polynomials - analyzemath.com


Factor Polynomials. ... Perfect cube x 3 + 3x 2 y + 3xy 2 + y 3 = (x + y) 3 11: ... As a practice, multiply (3x + 2)(3x - 1) ...
Read More At : www.analyzemath.com...

5 Rational Expressions, Equations, and Functions - Ace ...


... b31x - y2 1x - y2x + yDIVIDING RATIONAL EXPRESSIONSTo divide by a rational expression, multiply ... 2 + 10y + 41125y 3 - 82 , 15y - 22. a3b3. x ... 12x 2x 2 - 2x ...
Read More At : www.learningace.com...

(2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct.? - jiskha.com


Math(Please check my work.) (2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct.? this is a different problem... Here's how this one works out: .....x^2 + 5x - 3 ...
Read More At : www.jiskha.com...

Chapter 7 Rational Expressions and Functions - Ace ...


NThe LCD is fundamental propertyx (x - 2);546 Chapter 7 Rational Expressions ... 34x - 12x + 3=12x - 256x - 23x + 1x - 4=6x ... of a rational expression?Multiply or ...
Read More At : www.learningace.com...

Systems of Equations - Problems & Answers - Math10.com


Systems of Equations - Problems & Answers. ... {array}{|l} 6x - y = 11 \\ 12x - 2y ... {x-1}{3} + \frac{5y+1}{2} = \frac{x+10y-8}{6} \\ \frac{(x+2)(5y-2)}{2} = 5 ...
Read More At : www.math10.com...

Suggested Questions And Answer :


how to multiply rational expression of (x^2 + xy / 15y^3) (35y^2 / 6x+6y) (12x / 10y^2


Read More: ...

solve the linear system using any algebraic method 8x - 6y = 14 and 12x -9y = 18

8x-6y=14,12x-9y=18 Multiply each equation by the value that makes the coefficients of y equal.  This value is found by dividing the least common multiple of the coefficients of y by the current coefficient.  In this case, the least common multiple is 18. 3*(8x-6y=14)_2*(12x-9y=18) Multip
Read More: ...

3x³-2x²-19x-6/3x+1

((3x^(3)-2x^(2)-19x-6)/(3x+1)) Factor the polynomial using the rational roots theorem. (((x+(1)/(3))(x+2)(x-3))/(3x+1)) To add fractions, the denominators must be equal.  The denominators can be made equal by finding the least common denominator (LCD).  In this case, the LCD is 3.  
Read More: ...

how do you find the LCD of two rational expressions?

factoring
Read More: ...

How do you divide rational expressions?

Multiply the top and bottom by the common denominator of all the fractions. Doing this will get rid of the fractions within a fraction. I assume the % sign is supposed to mean ÷ x²  ---- -y ---------- 2y² ---- -x   x²  ---- (-xy) -y ---------- {
Read More: ...

solve the rational expression 4/(z+3)=2/(z-2)

4 / (z + 3) = 2 / (z - 2) So multiply both sides by (z + 3) and (z - 2), then you get:   4(z - 2) = 2(z + 3) Now multiply out the brackets: 4(z - 2) = 2(z + 3) => 4z - 8 = 2z + 6 Now subtract '2z' from both sides of the equation to get all the 'z' terms on the same si
Read More: ...

find a third degree polynomial equation with rational coefficients that has roots -4 and 6+i

A cubic equation always has three roots. These three roots are: 1) three real roots or, 2) 1 real root and two complex roots If one of the two complex roots is a + ib, then the other complex root is a - ib. We are given two of the roots as -4 and 6+i. Since one of the roots is c
Read More: ...

(2x^5y)^3 / 36x^8y^6

Simplify ——————— 36 Dividing exponents :  2.1    23   divided by   22   = 2(3 - 2) = 21 = 2 Equation at the end of step  2  : 2x 15y3 (—————— • x8) • y6 9
Read More: ...

how to solve this word problem

-12x^2+52x-35 -12x^2+52x-35 = (-2x+7)(6x-5) (-2x+7)(6x-5) = -2x*6x -2x(-5) + 7*6x + 7(-5)= - 12x^2 + 10x + 42x - 35 = - 12x^2 + 52x - 35
Read More: ...

express in simplest form, using positive rational exponents: 3x^-1/3(x^1/3-4x^4/3)

3x^(-1/3) * (x^(1/3) - 4x^(4/3)) = 3(x^(1/3) - 4x^(4/3)) / x^(1/3) = 3(x^((1/3) - (1/3)) - 4x^((4/3) - (1/3))) = 3(x^0 - 4x^(3/3)) = 3(1 - 4x^1) = 3(1 - 4x) = 3 - 12x
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1223 seconds